Optimization of celery leaf tea processing and the volatile components analysis. Issue 3 (21st January 2021) - Liu, Junchen; Cheng, Chenxia; Zhang, Zhiwei; Yang, Shaolan; Zhang, Xinfu
Abstract: In this study, celery leaves were used as materials to study the effects of different processing techniques on the quality of celery leaf tea. Sensory evaluation, GC–MS, and electronic nose analysis were used to identify the main aroma components of nine different processing techniques of tea. In sensory evaluation, sample No. 2 with green tea processing technology (fragrance enhancement at 80°C for 6 hr) was better popular in the processing of green tea. While the tea sample of No. 7 with oolong tea processing technology (fragrance enhancement at 80°C for 6 hr) was most suitable for the sense of the majority of the population. In the electronic nose measurement, the contents of aroma components in samples No. 2 and No. 7 were better than other samples. A total of 51 key aroma compounds were detected by GC–MS that could basically reflect the aroma characteristics of celery leaf tea. Practical applications: Celery ( Apium graveolens ) has many potential positive biological benefits. During the daily cooking process, the leaves of celery were usually thrown away as a by‐product of the initial processing of celery. But from a nutritional point of view, the nutritional value of celery leaves may exceed the celery stems. We process celery leaves into tea and determine the best process conditions for celery leaf tea processing. It is not only convenient for storage and transportation, but also retains the nutritional value of celery leaves.